Flood Hazard Mapping in Bone Regency Based on Geographic Information System (GIS) - Shaf, Shohifah; Mohammad Ikhwan Syahtaria; Christine Sri Marnani (International Journal of Technology and Education Research, 2026)
Bone Regency is one of the regions in South Sulawesi Province with a high-category flood disaster risk level, reaching a risk index of 164.46. This study aims to produce flood hazard mapping in Bone Regency using a Geographic Information System (GIS) approach and fuzzy logic. The methods employed include Geomorphic Flood Index (GFI) analysis to identify areas prone to inundation, as well as weighted overlay techniques based on slope and distance-from-river parameters. The research results indicate that the total area with flood hazard levels in Bone Regency reaches 93,773.14 ha, dominated by the high-hazard class covering approximately 75% of the total hazard potential. The spatial distribution shows the highest risk concentration in Mare Subdistrict (10,920.15 ha), Sibulue (9,062.06 ha), and Cenrana (6,968.28 ha). Model validation against historical data demonstrates an accuracy rate of 90%, proving that the integration of GIS and fuzzy logic is effective in mapping flood hazard zones with high precision. The results of this study are expected to serve as a strategic instrument for stakeholders in planning more effective and targeted disaster mitigation.